Occurrence, abundance, and distribution of microplastics pollution: an evidence in surface tropical water of Klang River estuary, Malaysia - Mohd Zaki, Muhammad Rozaimi; Peh, Xin Ying; Zainuddin, Azim Haziq; Razak, Muhammad Raznisyafiq; Aris, Ahmad Zaharin (Springer Netherlands, 2021)
Microplastics have been considered as contaminants of emerging concern due to ubiquity in the environment; however, the occurrence of microplastics in river estuaries is scarcely investigated. The Klang River estuary is an important ecosystem that receives various contaminants from urbanised, highly populated areas and the busiest maritime centre in Selangor, Malaysia. This study investigates the abundance and characteristics of microplastics in surface water of the Klang River estuary. The abundance of microplastics ranged from 0.5 to 4.5 particles L–1 with a mean abundance of 2.47 particles L–1. There is no correlation between the abundance of microplastics and physicochemical properties, while there is a strong correlation between salinity and conductivity. The microplastics were characterised with a stereomicroscope and attenuated total reflection–Fourier transform infrared spectroscopy to analyse size, shape, colour, and polymer composition. The microplastics in the surface water were predominantly in the 300–1000 μm size class, followed by > 1000 μm and < 300 μm, and were mostly transparent fibres, fragments, and pellets. Polyamide and polyethylene were the main polymer types in the composition of the microplastics, suggesting that the microplastics originated from heavily urbanised and industrial locations such as the port, jetty, and residential areas. The widespread occurrence of microplastics in the environment and subsequent penetration of aquatic food webs may pose a serious threat to organisms. This study provides baseline data and a framework for further investigation of microplastic contamination in estuaries.